Derivative prefixes to form nouns in Indonesian - Muhammad Wildan Fathurrohman; Hanifah Yulia P. S.; Isabella Enola D. A. K.; Tias Nur K. (Universitas Ahmad Dahlan, 2021)
This research discusses the variety of derivative prefixes that form nouns found in fiction, non-fiction, and news texts. The problem studied is the morphological process in the form of affixations (prefixes) forming Indonesian nouns from a derivation perspective. This research is a descriptive type with a qualitative approach. The data in this study are in the form of derivation prefixes that form nouns. The data collection technique uses the observing method andnote-taking technique, the observing method is used to review books and news texts carefully, while the note-taking technique is used to write in derivative prefixes to form nouns found in books and news texts. Furthermore, the data analysis technique was carried out by using the split method and technique for direct elements. After being analyzed based on the affix affixing process, the next process will be analyzed the class change process. The conclusion of this research is that there are four derivative prefixes to form nouns in Indonesian, namely the prefix ke-, pe-, per-, and se-. These derivativeprefixes function to form nouns from the base class of adverbs, adjectives, and verbs. The derivative pattern of noun-forming prefixes can be formulated as follows: ke- + Adv = N, ke- + A = N, ke- + V = N, pe- + A = N, pe- + V = N, per- + V = N, se- + A = N, and se- + V = N.